The Exchange Reamed Nailing technique in the treatment of aseptic tibial nonunion. A literature review of 371 cases - Cerone, Alessandro; Mastri, Pierluigi; Calvisi, Vittorio; Medici, Antonio; Fidanza, Andrea (Lo Scalpello - Journal, 2022)
The persistence of pain at the fracture site and the absence of bone callus at X-ray controls are the univocal criteria for diagnosis of nonunion. When this failure befalls, the healing process has stopped and the fracture is no longer able to consolidate without surgery. The aim of this review is to investigate the use and outcomes of the Exchange Reamed Nailing (ERN) technique for aseptic tibial shaft nonunion. Replacement surgery with an oversized reamed nail showed 91% success. After a tibial fracture, nonunion is to be expected in 17% of cases, with a majority of the hypertrophic type (82%). To avoid further failures, the following is essential: to increase the mechanical stability by implanting an oversize nail and lock it with 2 distal static screws and a proximal dynamic screw; to ream the canal to promote vascularisation with osteoinductive and osteoconductive effects; to ensure the absence of a latent infection, which can lead to osteomyelitis in 18% of failures. Autologous bone grafting and fibula osteotomy are useful in specific cases.